Examining the feasibility of a parental self‐help intervention for families awaiting pediatric eating disorder services. Issue 1 (26th October 2022) - Couturier, Jennifer; Sami, Sadaf; Nicula, Maria; Pellegrini, Danielle; Webb, Cheryl; Johnson, Natasha; Lock, James
Abstract: Objective: Waitlists for eating disorder (ED) services grew immensely during the COVID‐19 pandemic. To address this, we studied the feasibility of a novel parental self‐help waitlist intervention. Method: Parents of a child/adolescent (7–17 years) awaiting pediatric ED services were provided with our intervention, adapted from the family‐based treatment model, and consisting of videos and reading material with no therapist involvement. Parent‐reported child/adolescent weight was collected weekly 6 weeks pre‐intervention, 2 weeks during the intervention, and 6‐week post‐intervention. Recruitment and retention rates were calculated. Regression‐based interrupted time series analyses were completed to measure changes in the rate of weight gain. Results: Ninety‐seven parents were approached, and 30 agreed to participate (31% recruitment rate). All but one completed end‐of‐study measures (97% retention rate). The average rate of weight gain was 0.24 lbs/week pre‐intervention, which increased significantly to 0.78 lbs/week post‐intervention ( p < .034). Discussion: Our findings provide preliminary evidence that this intervention is feasible. Future research is needed to confirm the efficacy of this intervention on a larger scale. Public Significance: The COVID‐19 pandemic has resulted in several challenges in providing care for children and adolescents with eating disorders, including long waiting lists and delays in treatment. This study suggests that providing parents on a waitlist with educational videos and reading material is acceptable to parents, and may even help in improving the child's symptoms of an eating disorder.